Perspective of Turkish society toward autistic individuals: Personal experiences, knowledge, and interaction comfort - Gamze Alak (PLoS ONE, 2026)
Despite increasing awareness of autism spectrum disorder (ASD) and autistic individuals, factors shaping social interactions involving autistic individuals in the general population remain relatively underexplored. This study examined the interrelationships among personal experience, knowledge, and interaction comfort toward autistic individuals among Turkish adults and explored demographic differences. A total of 507 participants (aged 18+) were recruited using snowball sampling, and data were collected via an online survey. Data were analyzed using descriptive, comparative, and correlational analyses, followed by regression-based mediation and moderated mediation models (PROCESS macro). Participants primarily reported indirect experiences with autistic individuals, and both knowledge levels and interaction comfort were relatively high, with significant differences across several demographic characteristics. Interaction comfort was lower in social than in professional settings and varied according to levels of support needs. Knowledge mediated the relationship between personal experience and interaction comfort. The indirect effect was significant only at higher levels of interaction quality. These findings highlight the role of knowledge and interaction quality in shaping interaction comfort and suggest the importance of interventions that promote meaningful and informed interactions. Implications for future research and practice are discussed.